Ecohydrology and paleoenvironment of the Cretaceous (Albian) Cloverly Formation: insights from multi-taxon oxygen isotope analysis of vertebrate phosphates - Allen, M. L.; Suarez, M. B.; Adams, T. L.; Suarez, C. A. (Frontiers in Earth Science, 2025)
The Cloverly Formation of Montana and Wyoming preserves abundant nonmarine vertebrate fossils from the mid-Cretaceous, yet its paleoenvironment and faunal niche structure remain poorly understood. We analyzed δ18Οphosphate in over 100 fossil individuals from multiple vertebrate taxa collected from a single microfossil bonebed in Carbon County, Montana.To infer habitat preferences and water-use strategies, we compared δ18Οphosphate values within and across taxa. We reconstructed δ18Osurface_water from semi-aquatic reptile values using regressions calibrated with data from modern environments and extant taxa. Using a multi-taxon framework, we estimated warm-season water temperatures from δ18Osurface_water and δ18Οphosphate of lepisosteid (gar) scales, then converted these to air temperatures using a modern climate transfer function. δ18Οphosphate values ranged from 9.5‰ to 23.2‰ (VSMOW) and varied across taxa. Aquatic and semi-aquatic groups exhibited lower values than dinosaurian taxa. Our reconstructed mean δ18Osurface_water was −7.9‰ (95% CI: −10.1 to 5.5‰), yielding a warm-season water temperature of 26°C and an air temperature of 24°C. Intertaxon differences reflect niche partitioning and suggest primary isotopic signals are preserved. Unexpectedly high values in Bernissartiid-like neosuchian teeth may indicate greater ecohydrological diversity than previously recognized. Our δ18Osurface_water estimate aligns with other Aptian-Albian proxies but exceeds model-based predictions, likely due to outdated assumptions underlying the model. The MAWSAT estimate falls within the upper range of model-data assimilation outputs. These results provide new context for ecological structure in the Cloverly fauna and offer the first quantitative temperature estimate for the Formation, helping to define baseline conditions between the Aptian-Albian Cold Snap and the Cretaceous Thermal Maximum.